The Effect of Promotion and Image on Repurchase Decisions - Fathullah, Muhammad Falih; Nugroho, Dian Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this quantitative explanatory research is to identify the effects of sales promotion and brand image on the decision to repurchase the products of Standard Beef in Malang City. Using purposive sampling, 88 people who have bought the products of Standard Beef were selected as the respondents. The data was harvested via questionnaires and analyzed through multiple linear regression in SPSS version 23. This study finds that sales promotion partially has a significant impact on the decision to repurchase the products of Standard Beef, that brand image also partially has a significant influence on the decision to repurchase the products of Standard Beef, and that both sales promotion and brand image simultaneously affect the decision to repurchase the products of Standard Beef.